CGIAR Initiative on Agroecology: Technical report from the Kenya End-of-Initiative Results Dissemination Workshop - Adoyo, Beatrice; Awiti, Alex; Kuria, Anne; Chege, Christine Gacheri Kiria; Anyango, Edith; Fuchs, Lisa Elena; Guettou Djurfeldt, Nadia; Bolo, Peter; Wanyama, Rosina; Korir, Hezekiah; Nyawira, Sylvia; Onyango, Kevin (2024)
This report highlights key insights and lessons learned from the implementation of the CGIAR Initiative on Agroecology (AE-I) in Kenya. Launched in 2022, the AE-I concluded with a results dissemination workshop on December 10, 2024, at the ICRAF Campus in Nairobi. The event brought together 89 in-person attendees and 331 virtual participants. Alongside presenting findings from the Initiative’s six work packages, the workshop benefited from candid feedback and recommendations from diverse stakeholders on advancing agroecological transitions. The workshop featured a mix of presentations by project leaders, partners, government representatives, plenary, and panel discussions, addressing critical topics such as research outcomes, government commitment to agroecological transitions, unlocking financing and market opportunities to strengthen resilient food systems, and mobilizing farmers to accelerate transitions. The findings underscored agroecology as an economically viable initiative with the potential to enhance resilient and inclusive food systems. Raising awareness of agroecology’s holistic benefits through clear, simple, and tailored communication to stakeholders, including farmers and policymakers, was identified as a key strategy for promoting its adoption and scaling. To ensure ownership and sustained implementation, the report emphasizes the importance of principle-driven partnerships, enabling the co-design of agroecological innovations that meet societal needs. While an inclusive approach—incorporating all actors in the food system value chain—was noted to foster holistic transitions, it was highlighted that agroecological transitions are dynamic processes shaped by diverse factors. Key drivers of these transitions include consumer behavior and market demand, climate change, health concerns, input costs, capacity building, and innovation, with the cost of ecological inputs identified as a primary factor. Additionally, the promotion of high-input industrial agriculture and the underutilization of organic resources called for incentivizing public and private investments in agroecological interventions. Enabling institutional environments, including supportive policies and secure land tenure, were recognized as central to advancing transitions. However, while Kenya boasts in agroecological provisions with several counties developing agroecology related policies, these efforts were reported to be fragmented and lacking alignment within a centralized policy framework, limiting effective and sustained implementation. Developing a unified policy framework to ensure consistency, alignment, and efficiency in agroecological transitions was therefore proposed.